Inter-observer reliability of a scoring system to evaluate bruises on turkey carcasses - Raederscheidt, Luisa; Kaufmann, Falko; Spindler, Birgit; Kemper, Nicole; Andersson, Robby (Frontiers in Animal Science, 2024)
Traumatic injuries such as bruises have been considered as an important indicator to assess animal welfare in livestock farming. The possibility to assign the injury to a particular stage or moment in the production process may allow judgements on possible causes and thus reduce its prevalence. Currently, there is no consistent definition or scoring system for bruised poultry carcasses in German meat-inspection and the prevalence is affected by the variability of scoring systems as well as the observer bias. Therefore, the objective of this study was to determine the inter-observer reliability of bruise characteristics at the slaughter line and to validate the findings with measurements of bruises and photographed carcasses. Inter-observer reliability was assessed with two observers who each scored 10,880 turkey carcasses simultaneously at a running slaughter line after a short training. The strength of agreement was "good" for the total number of detected bruises and number of bruises on breast, wings and legs per flock (ICC = 0.81 -0.88). Agreement (ICC) on the number of small, medium and large bruises ranged between "good" and "moderate" values (0.70 -0.84), whereas number of bruises in the different colors showed "moderate to poor" reliability (0.04 -0.64). Additionally, agreement on bruise characteristics was tested on photographs (n= 513 carcasses) without time limit. Highest agreement between observers was found for location of bruises (Kw = 0.98). Again, color of the bruises showed the lowest agreement (Kw = 0.36), whereas it was "moderate" for the size of bruises (Kw = 0.45). When comparing each observers' scoring values for size with size measurements (digital analysis) of bruises, the observers tended to underestimate the actual size. Overall, the total number of detected bruises and the location of bruises showed the highest agreement between observers at the slaughter line and on photographs indicating reliable variables. However, as the variable color showed a low agreement, a standardized objective method should be developed to objectively assess bruise prevalence and characteristics.